(3GdeUGHjM aj TQM GdeaGJjMs - (3GdHgHgGfj, GdCSJGP GdCcHQ, GdhMjO, eMeO HGbQ Hf eMeO Cced, (B1206 (3g`s ((3EHQGgje GdeMeOs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3GdCMcGe GdTQYjI HCSQgG JhbjajI ehbhaI Ydi GdKHhJ ef GdTQY HGdHOjgI ShGA cGfJ aj GdYHGOGJ Ch GdeYGedGJ hCeG ehVhYGJgG agj YHGQI Yf (B...s
(3BNQgG (B:s
... (3ajchf GdeQGO aj bhdg hEPG de jONdhG efGRdge de jRhQ GdHjJ (B..(3cGdUMjMI hYdi JbOjQ XghQgG ajeG jXgQ aj GdehKbI HGdLhGH YfgeG (B...s
(3GdJGQjN ef GdLRA GdKGfj ef faS GdfSNIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\49s
(3GdPQjYI (B21 - 53 (4037 )s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis